Rudimentary Meningocele of the Scalp: A Pitfall in the Diagnosis of Vascular Neoplasms - Subramaniam Ramkumar (Case Reports in Pathology, 2018)
We present a case of sequestrated meningocele in a 1-year-old girl, who presented with a 1x1cm occipital swelling since birth. CT brain revealed the soft tissue swelling to be extracranial. She underwent surgical excision of the specimen and the excised mass was sent for histopathological examination. The specimen consisted of skin and subcutaneous tissue measuring 2 x 1 x 1 cm. The entire tissue was paraffin processed. Multiple sections studied from the lesion showed an ill circumscribed locally infiltrative dermal lesion. The lesion was composed of whorled proliferations of meningothelial cells enclosing pseudovascular spaces. Immunohistochemically the lesion was positive for EMA, Desmin, and negative for endothelial markers. The present case was documented as a rare case of a rudimentary meningocele.